La universidad y su gestión de la comunicación - Andrade Vargas, Adrián (2019)
The present investigation is oriented towards the analysis of the internal communication in the institutional image of the Vicente Roca Fuerte Secular University and its impact on the students of the career of journalism, for this it was approached from a mixed approach, hich combined qualitative and quantitative techniques in a field environment, where the social actors of the university work gave their opinions and perspectives regarding the functioning of the internal communication in the university, being these the most involved in this process. Interviews were applied to several professors of the Journalism Career and surveys to a sample of 186 students. The results showed that the university needs to rethink internal communication processes and to be more open to the new dynamics imposed by current reality. That the processes must be evaluated, they show difficulties in internal communication…..